Ultrafast transmission electron microscope for studying the dynamics of the processes induced by femtosecond laser beams. (March 2017) - Andreev, S.V.; Aseev, S.A.; Bagratashvili, V.N.; Vorob'ev, N.S.; Ishchenko, A.A.; Kompanets, V.O.; Malinovsky, A.L.; Mironov, B.N.; Timofeev, A.A.; Chekalin, S.V.; Shashkov, E.V.; Ryabov, E.A.
Abstract: We have developed an ultrafast transmission electron microscope for studying dynamic processes in samples excited by femtosecond laser pulses and for probing transient processes occurring under irradiation by a pulsed (~7 ps) photoelectron beam with an adjustable delay with respect to the excitation pulse. A 75-keV photoelectron beam is formed using a silver photocathode irradiated by a femtosecond laser beam. This microscope is shown to have a high spatial resolution in the photoelectron regime: nanoscale in the imaging regime and atomic in the electron diffraction regime. It is used for experimental observation of ultrafast interaction of a laser-induced electron cloud with a pulsed photoelectron beam. Using this effect, a method of spatial and temporal alignment of excitation laser and probe electron pulsed beams on a sample is experimentally implemented.